A public health value-based healthcare paradigm for HIV - Sebastian Vermeersch; Rémy P. Demeester; Nathalie Ausselet; Steven Callens; Paul De Munter; Eric Florence; Jean-Christophe Goffard; Sophie Henrard; Patrick Lacor; Peter Messiaen; Agnès Libois; Lucie Seyler; et al. (BMC, 2022)
Abstract Background HIV patients face considerable acute and chronic healthcare needs and battling the HIV epidemic remains of the utmost importance. By focusing on health outcomes in relation to the cost of care, value-based healthcare (VBHC) proposes a strategy to optimize quality of care and cost-efficiency. Its implementation may provide an answer to the increasing pressure to optimize spending in healthcare while improving patient outcomes. This paper describes a pragmatic value-based healthcare framework for HIV care. Methods A value-based HIV healthcare framework was developed during a series of roundtable discussions bringing together 16 clinical stakeholder representatives from the Belgian HIV reference centers and 2 VBHC specialists. Each round of discussions was focused on a central question translating a concept or idea to the next level of practical implementation: 1) how can VBHC principles be translated into value-based HIV care drivers; 2) how can these value-based HIV care divers be translated into value-based care objectives and activities; and 3) how can value-based HIV care objectives and activities be translated into value-based care indicators. Value drivers were linked to concrete objectives and activities using a logical framework approach. Finally, specific, measurable, and acceptable structure, process and outcomes indicators were defined to complement the framework. Results Our framework identifies 4 core value areas where HIV care would benefit most from improvements: Prevention, improvement of the cascade of care, providing patient-centered HIV care and sustaining a state-of-the-art HIV disease management context. These 4 core value areas were translated into 12 actionable core value objectives. For each objective, example activities were proposed. Indicators are suggested for each level of the framework (outcome indicators for value areas and objectives, process indicators for suggested activities). Conclusions This framework approach outlines how to define a patient- and public health centered value-based HIV care paradigm. It proposes how to translate core value drivers to practical objectives and activities and suggests defining indicators that can be used to track and improve the framework's implementation in practice.